a) 200 + 300 x 2 - 100 + ( -100)
= 200 + 600 - 100 + ( -100 )
= 800 - 100 + ( -100 )
= 700 + ( -100 )
= 600
b) 500 - 100 x 3 + ( -13 )
= 500 - 300 + ( -13 )
= 200 + ( -13 )
= 187
a ) 200 + 300 x 2 - 100 + ( - 100 )
= 200 + 600 - 100 + ( - 100 )
= 800 - 100 + ( - 100 )
= 700 + ( - 100 )
= 600
b ) 500 - 100 x 3 + ( - 13 )
= 500 - 300 + ( - 13 )
= 200 + ( - 13 )
= 187
a ) 200 + 300 x 2 - 100 + ( - 100 )
= 200 + 600 - 100 + ( - 100 )
= 800 - 100 + ( - 100 )
= 700 + ( - 100 )
= 600
b ) 500 - 100 x 3 + ( - 13 )
= 500 - 300 + ( - 13 )
= 200 + ( - 13 )
= 187
a) 200 + 600 - 100 + ( -100 )= 800-100 + (-100)= 700+ (-100)= 600
b) 500 - 300 + (-13)= 200 +(-13)= -187
k cho mình nhé
a) 200+300 x2 -100 + (-100)
= 200 + 600 - [ 100 + (-100)]
=200 + 600 - 0
=800
b) 500 - 100 x3 + (-`13)
=500 - 300 + (-13)
=187
200 + 300 x 2 - 100 + ( - 100)
200 + 600 - 100 + (-100)
= 800 - 100 + ( - 100)
= 700 + (-100)
= 600
500 - 100 x 3+ ( - 13)
= 400 x 3 + (-13)
= 1200 + (- 13)
= 1187